2014
DOI: 10.1007/s10637-014-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative cytotoxic agent withaferin A resensitizes temozolomide-resistant glioblastomas via MGMT depletion and induces apoptosis through Akt/mTOR pathway inhibitory modulation

Abstract: Temozolomide (TMZ) has remained the chemotherapy of choice in patients with glioblastoma multiforme (GBM) primarily due to the lack of more effective drugs. Tumors, however, quickly develop resistance to this line of treatment creating a critical need for alternative approaches and strategies to resensitize the cells. Withaferin A (WA), a steroidal lactone derived from several genera of the Solanaceae plant family has previously demonstrated potent anti-cancer activity in multiple tumor models. Here, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 67 publications
2
43
0
Order By: Relevance
“…Concentration‐dependent growth‐suppressive effects were confirmed in all cell lines studied, and the IC 50 values ranged from 60 to 200 nM at 72 h (Fig. ), which are lower than the range of IC 50 values reported for other cancer cell lines (300 to 1000 nM at 72 h), suggesting that human leukemia cell lines are comparatively highly susceptible to WA. WA treatment also resulted in an increased number of mitotic cells, and the cell cycle analysis showed that WA induces G2/M arrest (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Concentration‐dependent growth‐suppressive effects were confirmed in all cell lines studied, and the IC 50 values ranged from 60 to 200 nM at 72 h (Fig. ), which are lower than the range of IC 50 values reported for other cancer cell lines (300 to 1000 nM at 72 h), suggesting that human leukemia cell lines are comparatively highly susceptible to WA. WA treatment also resulted in an increased number of mitotic cells, and the cell cycle analysis showed that WA induces G2/M arrest (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Previous reports have demonstrated that WA affects microtubules or vimentin intermediate filaments and, subsequently, exerts cytotoxicity or inhibition of the epithelial–mesenchymal transition . WA is reported to induce cell cycle arrest at G2/M phase, resulting in apoptosis . Nonetheless, the detailed mechanisms of action remain to be determined and may be different depending on the cells, tissues or experimental systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of our results, others' studies also found that HSF1 rises were not followed by enhanced HSP70 expression. 31,32) Recently, cytoprotective functions of HSPs, particularly HSP70, have been connected to MAPKs signaling pathway. 33,34) For this reason, we investigated whether there is involvement of MAPKs in the induction of HSP70 by Z-ligustilide.…”
Section: Discussionmentioning
confidence: 99%
“…Current research looks at combining WA and TMZ, which shows promise by allowing resistant cells to become sensitized and undergo apoptosis [39,40]. WA treatment acts by depleting MGMT, enabling TMZ to cause DNA damage, G2/M cell cycle arrest, and death in cancerous cells [41].…”
Section: Safety Considerationsmentioning
confidence: 99%